Consumer economics : issues and behaviors. - Goldsmith, Elizabeth B., ....- (Upper Saddle River : Pearson, 2009)
This book provides an up-to-date look at the consumer movement and the intricacies of consumer behavior. It addresses who buys what, how, when, and why. It also looks at the forces that impact consumer choice in an ever-changing and often turbulent world-all using a balanced casebook approach. This edition emphasizes the consumer power model, includes more on personal finance and reflects the latest consumption shifts and impact consumers have on product development, advertising, packaging and promotion.Anyone interested in consumer behavior.